AGEING AND THE AMOUNT OF DNA EXTRACTED FROM BAWEAN DEER (A xis kuhlii ) FECES - Adi Nugroho; Denni Susanto; Sena Adi Subrata (SEAMEO BIOTROP, 2022)
Noninvasive genetic sampling is the most reliable approach to collect endangered species which are typically rare and elusive. However, the approach is hampered by poor quality and quantity of DNA amount, and therefore, a pilot study is required. Our current short communication article reports the first noninvasive genetic sampling approach using feces of critically endangered Bawean deer (Axis kuhlii) to test the effect of aging on the amount of DNA extraction. Fecal samples of the Bawean deer were collected from the Bawean Deer Captive Unit in Sangkapura Village, Bawean Island, East Java. The samples were grouped into two different categories, namely: 1) New samples: for feces that had just been expelled for less than a day and 2) Old samples: for feces that were estimated to have been expelled for more than a day. There were 11 New samples and 16 Old samples. The samples were extracted using the QIAGEN Mini Stool Kit. The DNA quantification was carried out by using a fluorometer. The results of the extraction between the two categories were analyzed by the Kruskal Wallis test. The results showed that the mean rank value of the New samples was better (15.27) than the Old samples (13.13). The P value of the Kruskal Wallis test, however, was higher than the Asymp significant value, indicating that there was no meaningful differences (P = 0.49) between the two samples categories. The work described in this short communication article is a preliminary result and an important step in the study of Bawean deer population genetic.